Bendamustine for relapsed blastic plasmacytoid dendritic cell leukaemia. Issue 2 (8th October 2015) - Bétrian, Sarah; Guenounou, Sarah; Luquet, Isabelle; Demur, Cécile; Huynh, Anne; Ysebaert, Loïc; Recher, Christian; Huguet, Françoise
Abstract: Optimal treatment of blastic plasmacytoid dendritic cell neoplasm (BPDCN), a rare entity of dismal prognosis previously described as CD4+/CD56+ hematodermic malignancies, is not defined. We report five cases of relapsed BPDCN treated with bendamustine hydrochloride, a well‐tolerated bifunctional drug acting as an alkylating and antimetabolite agent. All patients were above the age of 50 years and in advanced disease (early first relapse in two, subsequent relapse in three; multi‐organ involvement in four; previous intensive chemotherapy in five; and stem cell transplantation in four). Four patients were evaluable for response. Two failed therapy, one died from tumor lysis syndrome after rapid blast clearance from blood, and one reached and maintained complete remission for 7 months. Bendamustine should be further evaluated in BPDCN. Copyright © 2015 John Wiley & Sons, Ltd.